2013
DOI: 10.3171/2012.11.jns121038
|View full text |Cite
|
Sign up to set email alerts
|

Timing and mechanism of ischemic stroke due to extracranial blunt traumatic cerebrovascular injury

Abstract: Most ischemic strokes due to TCVI are embolic in nature and occur prior to screening CTA and initiation of treatment with aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 40 publications
(57 reference statements)
4
71
1
Order By: Relevance
“…10 Griessenauer et al concluded that most ischemic strokes occur before initial screening with CTA, and prior to treatment with an antiplatelet medication, indicating that follow-up imaging may not aid in preventing most ischemic strokes. 12 We have noticed similar findings thus far in our BCVI analysis, with the majority of strokes presenting soon after admission, and frequently prior to the administration of any medication. 25 Similarly, Mayberry et al retrospectively examined cases treated in 2 major trauma centers and noted that all strokes from BCI happened within 12 hours of admission.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…10 Griessenauer et al concluded that most ischemic strokes occur before initial screening with CTA, and prior to treatment with an antiplatelet medication, indicating that follow-up imaging may not aid in preventing most ischemic strokes. 12 We have noticed similar findings thus far in our BCVI analysis, with the majority of strokes presenting soon after admission, and frequently prior to the administration of any medication. 25 Similarly, Mayberry et al retrospectively examined cases treated in 2 major trauma centers and noted that all strokes from BCI happened within 12 hours of admission.…”
Section: Discussionsupporting
confidence: 67%
“…From the available literature, however, it is difficult to determine the true rate of BCVIrelated ischemic strokes; there have been reports as low as 0.05% and as high as 50%. 10,12,14,16 In this current study examining low-grade BCI, we identified only 1 patient (1%) who presented with a BCI-related stroke, which is not a dissimilar finding from our earlier report on low-grade BVIs. 25 A previous study from our institution by Eastman et al examined 26 patients with either BCIs and/or BVIs (4 of those patients had a Grade 1 or 2 BCI) and found a stroke rate of 3.8% (1 of 26) in patients with BCVI.…”
Section: Discussioncontrasting
confidence: 33%
See 2 more Smart Citations
“…When necessary, digital arteriography can be used to provide a clearer picture of the extent of arterial injury. 8 Treatment can be administered via percutaneous access, by embolization or by placement of a covered stent. [9][10][11] Conventional techniques for vascular repair include identification of the orifice allowing communication between artery and vein -of which there is generally only one -followed by a number of possibilities, including lateral suture, end-to-end anastomosis, interposition of a vein graft, repair using patches and ligature.…”
Section: Introductionmentioning
confidence: 99%